Impact of β-blockers on mortality in critically Ill patients with type 2 myocardial infarction: insights from a retrospective cohort study - Tang, Shanshan; Wu, Chengcheng; Wang, Haixiang; Gao, Zhuoting; Li, Yongle (Frontiers in Cardiovascular Medicine, 2025)
BackgroundType 2 myocardial infarction (T2MI) is common in critically ill patients, is associated with high mortality. However, the effect of β-blocker therapy on mortality remains uncertain.ObjectiveTo evaluate the impact of β-blockers on short-term and long-term mortality in intensive care unit (ICU) patients with T2MI.MethodsThis retrospective study analyzed 1,636 T2MI patients from the MIMIC-IV database. Propensity score matching (PSM) adjusted for confounders, resulting in 489 matched pairs. Mortality risks were analyzed using multivariable regression models, with subgroup and sensitivity analyses validating findings.ResultsBefore PSM, in-hospital, 30-day, and 1-year mortality rates were 13.3%, 17.2%, and 34.1%. Kaplan–Meier survival analysis demonstrated significantly higher survival probability in the β-blocker group (log-rank test, P < 0.001). After propensity score matching to balance baseline characteristics, multivariable regression analysis demonstrated that β-blocker therapy was associated with a 45% reduction in in-hospital mortality [odds ratio (OR): 0.55, 95% confidence interval (CI): 0.38–0.82], a 36% reduction in 30-day mortality [hazard ratio (HR): 0.64, 95% CI: 0.48–0.84], and a 27% reduction in 1-year mortality (HR: 0.73, 95% CI: 0.61–0.88). Sensitivity analyses supported the robustness of these results.Conclusionsβ-blockers significantly reduce mortality in critically ill T2MI patients, supporting their use as a key treatment strategy for this population.